Automatic Weather Station Observations of the April 2014 Mount Everest Avalanche. Issue 2 (1st May 2017) - Moore, G. W. K.; Cristofanelli, Paolo; Bonasoni, Paolo; Verza, Gian Pietro; Semple, J. L.
ABSTRACT: Instrumental records indicate a warming of approximately 0.8 °C has occurred in the Mount Everest region since the 1980s, which has resulted in a 100–300 m rise in the height at which the ground is permanently frozen as well as a retreat and thinning of Everest's glaciers. For some time, there have been concerns that this warming and the resultant changes in the region's glaciers may be increasing the risks for travellers to Mount Everest as well as the indigenous populations who support them. On 18 April 2014, an avalanche caused by the collapse of a large serac swept down Mount Everest's Khumbu Ice Fall resulting in the deaths of 16 Sherpa. Although satellite imagery has been used to estimate the size of the serac, in situ data on the avalanche itself has not been available. Here we show that this event coincided with an approximate 15-min-long wind, thermal, and moisture anomaly, which was observed at the Nepal Climate Observatory-Pyramid situated 10 km from Mount Everest. We argue that this anomaly was associated with the avalanche and thereby provides some information on its scale and duration as well as a potential mechanism to monitor future events in this remote and data-sparse region.